Research on the Combination of Mobile Communication Technology and Computer Internet Technology - Feng, Yuan (Journal of physics. Conference series, 2021)
The integration of Internet tech and mobile communication tech has changed the form of traditional info and communication tech, which can better serve the real needs of people for real-time communication and high-speed sharing and interconnection of data, info and resources. Based on this, this paper first analyses the connotation and characteristics of mobile communication and computer Internet, then studies the integration mode of mobile communication tech and computer Internet tech, and finally gives the trend of the combination of mobile communication tech and computer Internet tech.